Levels of 25(OH)D3, IL-2, and C-peptide in Children with Type 1 Diabetes Mellitus (T1DM) Receiving Vitamin D3 Supplementation - Tjahyo Suryanto; Harjoedi Adji Tjahjono; Edi Widjajanto (Journal of Tropical Life Science, 2018)
Type 1 Diabetes Mellitus (T1DM) has become a health problem in many countries. T1DM is the consequence of autoimmune destruction process of Î² cells. There was relationship between vitamin D deficiency with T1DM. The destruction process was caused by an imbalance of pro-inflammatory and anti-inflammatory cytokines. One of the pro-inflammatory cytokines is IL-2. C-peptide examination to see the function of beta cells due to destruction of pancreatic beta cell. Administration of vitamin D3 supplementation still cause controversy and give varying results. This randomized clinical trial was conducted to determine the levels of 25(OH)D3, IL-2, and C-peptide in people with T1DM who received vitamin D3 supplementation. The subjects were 26 children with T1DM, divided into K1 group (received vitamin D3 supplementation) and K2 group (received placebo). The results showed higher levels of 25(OH)D3 in the K1 group and statistically found a significant difference (p = 0.00). Higher levels of IL-2 and lower C-peptide were obtained in the K1 group and no statistically significant differences were found (p = 0.76 and p= 0.26). The insignificant relationship and the negative correlation were found between 25(OH)D3 and IL-2 (p = 0.71; r = - 0.12), 25(OH)D3 and C-peptide (p = 0.59; r = -0.16), also levels of IL-2 and C-peptide (p = 0.13; r = -0.44) in children with type 1 diabetes who received vitamin D3 supplementation. From this study can be concluded that administration vitamin D3 supplementation in patients with T1DM can increase levels 25(OH)D3 significantly. This increase has not significantly lowered levels of IL-2 and increased levels of C-peptide. However, there was an absolute decrease in the rate of slower C-peptide in the supplemented group than in the placebo group.